2014
DOI: 10.1007/s00595-014-0978-1
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcomes of endovascular repair for abdominal aortic aneurysms with the on-label use compared with the off-label use of an endoprosthesis

Abstract: Most midterm outcomes of EVAR in which the endografts were used off-label were similar to those associated with on-label use of the devices. Off-label use of EVAR endoprostheses is feasible, but requires the use of special techniques in patients with challenging anatomical features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
1
18
1
Order By: Relevance
“…14,15 The "pave and crack" technique has been proposed as a minimally invasive alternative to open retroperitoneal exposure of the access vessels when the other endovascular techniques described above fail to overcome access difficulties. 5,16 This approach may possibly eliminate the need for open surgical ilio-femoral conduits as shown in the current series where no anatomical restrictions were assumed to limit the applicability of the EC. However, this policy can make the procedure more challenging when the anatomical complexity of the iliac occlusive disease increases, such as with highly calcified occlusions combined with tortuosity.…”
Section: Discussionmentioning
confidence: 80%
“…14,15 The "pave and crack" technique has been proposed as a minimally invasive alternative to open retroperitoneal exposure of the access vessels when the other endovascular techniques described above fail to overcome access difficulties. 5,16 This approach may possibly eliminate the need for open surgical ilio-femoral conduits as shown in the current series where no anatomical restrictions were assumed to limit the applicability of the EC. However, this policy can make the procedure more challenging when the anatomical complexity of the iliac occlusive disease increases, such as with highly calcified occlusions combined with tortuosity.…”
Section: Discussionmentioning
confidence: 80%
“…Before this study, Schanzer et al found potential IFU adherence as high as 69% and as low as 42% based on preoperative imaging without knowledge of device use, with other smaller but more detailed studies showing IFU adherence between 69.3% and 58.1%. [7][8][9][10][11][12] Our observation of fewer patients being treated within IFU compared with earlier studies likely reflects the realities of patient presentation at an institution referred a large percentage of patients with more challenging anatomy. In addition, a long-standing investigational device exemption meant it was more likely that many patients had devices placed outside IFU, especially earlier in the studied period.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have attempted to look at the relationship between adherence to IFU and EVAR outcomes, but as of yet, there has failed to be a consensus on the matter. [6][7][8][9][10][11] In this study, we examined detailed anatomic as well as clinical data in an institutionally maintained database of patients undergoing EVAR to determine the effects of IFU adherence on patient outcomes.…”
mentioning
confidence: 99%
“…35 Iliac conduits (ie, "crack and pave" technique with endo-conduits and open retroperitoneal exposure and graft placement) have been adopted in order to establish adequate access and facilitate endovascular interventions. 36,37 Previous studies have shown that iliac conduits are required in 7.1% to 13.4% of abdominal aortic aneurysm repairs, 14,38 while 10% of thoracic endovascular aortic repairs (TEVAR) need an iliac conduit. 16 In this study, the combined iliac conduit utilization rate to treat abdominal and/or thoracic aortic pathologies was 17%.…”
Section: Discussionmentioning
confidence: 99%